Digital Pragmatics: Analysis of Communication Skill Speech Acts in Indonesian Teenagers' - Nur Afifah; Eli Marlina Harahap; Nikmah Hasibuan; Husniah Ramadhani Pulungan; Devinna Riskiana; Isthifa Kemal (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the use of speech acts by Indonesian adolescents in digital communication, particularly through comments on social media platforms such as Instagram and TikTok. The study aims to identify the types of speech acts commonly used, examine how the digital context influences the forms and strategies of these utterances, and explore the socio-cultural meanings embedded in these interactions. A qualitative descriptive method was used with data collected from 150 naturalistic comments made by adolescents aged 13–19. The analysis was conducted using Searle's speech act theory, focusing on contextual categorization and interpretation. The findings indicate that representative and expressive speech acts are the most frequently used, followed by directive, commissive, and declarative speech acts. The digital environment shapes linguistic expression through unique features such as emoticons, informal spelling, and visual-emotional reinforcers. These linguistic choices are influenced by the immediate, informal, and performative nature of online interactions. The results also indicate that speech acts on social media reflect adolescents' construction of identity, group affiliation, and shared cultural norms in the digital space. This study concludes that social media serves not only as a communication tool but also as a platform for socio-cultural expression among adolescents. Further studies could explore variations in usage across platforms or different demographic groups.